'This was different': transferring climate mitigation knowledge practices south to south with the MAPS programme. (21st October 2018) - Kane, Lisa; Boulle, Michael
ABSTRACT: This article is a case study of the Mitigation Action Plans and Scenarios programme (MAPS) which worked in climate change mitigation and development policy-making spaces in Brazil, Chile, Colombia, Peru and South Africa from 2010–2015. The MAPS programme was focused on achieving change in the commitment of southern decision makers to mitigate against climate change through government-mandated, stakeholder processes which generated evidence making a case for a low carbon transition. The article draws on reflective materials generated in the last year of the project. The value of MAPS was found in the well-tested data and evidence-driven scenario building; locally specific and country-driven processes; a culture of knowledge sharing through facilitated communities of practice; the role of professional facilitation in process design and in conducting stakeholder processes; shared experiences of working in the south, and particularly with cultural differences and conflict; and new ways of working south–south with each other, and with donors. These MAPS programme experiences stood in contrast to previous north–south knowledge sharing involvements. Theoretically, the article asks whether MAPS represents southern theory-making (after Connell, 2007). It concludes that through the action-oriented, facilitated co-production way of working on climate change in the south, MAPS represents an understanding of southern theory that challenges the orthodoxy of global knowledge production. MAPS emphasizes the need for theorizing in, and of, the south, and connecting policy and practices. Key policy insights Climate change mitigation work in the south faces poorly resourced, fragmented, under-capacitated governance structures, often in conflicted settings. Given conflicted settings, skilled facilitation is an integral part of knowledge-making processes. Strong local communities of practice, who undertake learning-by-doing and are connected to 'stubborn' development realities, are also key to knowledge-making. Intentional co-production of data and evidence enable peer-to-peer learning and the trust-building which is vital to strong communities of practice.